Has regulatory capital made banks safer? Skin in the game vs moral hazard - Ernest Dautović (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
The paper evaluates the impact of macroprudential capital regulation on bank capital, risk taking behaviour, and solvency. The identification relies on the policy change in bank-level capital requirements across systemically important banks in Europe. A one percentage point hike in capital requirements leads to an average CET1 capital increase of 13 percent and no evidence of reduction in assets. The increase in capital comes at a cost. The paper documents robust evidence on the existence of substitution effects toward riskier assets. The risk taking behavior is predominantly driven by large and less profitable banks: large wholesale funded banks show less risk taking, and large banks relying on internal ratings based approach successfully disguise their risk taking. In terms of overall impact on solvency, the higher risk taking crowds-out the positive effect of increased capital.
Keywords: E51; G21; O52; 330; capital requirements; risk-taking; moral hazard; macroprudential policy